Need to Strengthen Availability of Right Based Family Planning Services (International Journal of Scientific Research and Management (IJSRM), 2017)
Availability and access to quality family planning & contraception services helps in improving overall health & well-being of people. Family planning programmes are also very efficient and effective in reducing the mortalities & and have demonstrable impact in reducing poverty. Still, people in developing countries specially girls & women faces lot of difficulties in accessing family planning services including lack of knowledge about family planning services & methods and lack of availability. Right to family planning services is an important part of Reproductive rights and different human right documents & treaties include the provision of family planning services as a right of the individual. However still, millions in developing countries are denied of their rights of family planning and contraception services. There is need to address these human right violations through improving availability and accessibility to right based family planning services